Common disorders in the neurological emergency room - experience at a tertiary care hospital - Rizos, Timolaos; Jüttler, Eric; Sykora, Marek; Poli, Sven; Ringleb, Peter A. (European journal of neurology, 2011)
Background: The profile of patients with neurological diseases referred to specialized emergency rooms (ER) has not been reported and it is unknown whether a setting of decentralized ERs is associated with a high number of referrals because of inappropriate admissions. Methods: In this prospective study, consecutive patients of a specialized neurological ER were enrolled. Data encompassed time from symptom onset to admission, discharge diagnoses, data on hospitalization and on transfers to and from other ERs. Results: Thousand seven hundred and forty-three patients were enrolled. Most common diagnoses were cerebrovascular events (26.5%), headache disorders (13%) and seizures (12.7%). Time since onset of symptoms depended on who referred the patient (P < 0.001); seizure patients presented earlier than other patients (P < 0.001) and 30.5% of patients with cerebrovascular events presented within 3 h after symptom onset but did not present sooner than patients with other diagnoses. In 18%, diagnoses did not match neurological disorders, 4.5% of patients suffered from cardiovascular events. Referrals to and from other ERs rarely occurred (10.3% vs. 5.9%). Only 20 patients with acute cerebrovascular events were referred via other ERs (1.1%). Conclusion: A system of a specialized neurological ER can quickly clear up uncertainties in interpreting neurological symptoms. Owing to the rising number of neurological patients in ERs, more studies are urgently needed comparing the different organizational forms for emergency services.
Gesehen am 16.09.2022